Mechanism and optimization of supramolecular complexation‐enhanced fluorescence spectroscopy for the determination of SN‐38 in plasma and cells. (19th November 2020) - Zhao, Kena; Guo, Tao; Sun, Xian; Xiong, Ting; Ren, Xiaohong; Wu, Li; Yang, Rui; Sun, Huimin; Shi, Senlin; Zhang, Jiwen
Abstract: Quantitative detection of two different forms of SN‐38 in biological samples is, currently, cumbersome and difficult. A revisit to the mechanism of supramolecular complexation‐enhanced fluorescence spectroscopy helps to optimize the determination of SN‐38 in plasma and the cellular pharmacokinetics in A549 cells based on the supramolecular complexation. Firstly, the inclusion mechanism dominated by thermodynamic constants was determined by measuring kinetic/thermodynamic parameters ( k on, k off, Δ G, Δ H, Δ S ). On this basis, the best effect of fluorescence sensitization was optimized through screening the interaction conditions (cyclodextrin species and concentrations, drug levels, temperature, pH of the buffer, and reaction time). Furthermore, the proportional relationship between the concentration of the inclusion complex and the fluorescence intensity was confirmed. Finally, a highly sensitive, selective spectrofluorimetric method was established and validated for quantitative analysis of the lactone and carboxylate molecular states of SN‐38 plasma levels in rats and cell membrane transfer kinetics in A549 cell lines. The limits of detection for the lactone and carboxylate forms in plasma were found to be 0.44 ng·ml −1 and 0.28 ng·ml −1, respectively. Precision and accuracy met the requirements of biological samples analysis. The proposed detection method provided a reference for elucidating the biodistribution of SN‐38. Abstract : SN‐38 combined with SBE‐β‐CD under acid medium can cause fluorescence sensitization while, under alkaline medium, the lactone ring of SN‐38 is transformed into an open carboxylate structure without fluorescence sensitization. Based on this characteristic, a CD‐induced spectrofluorimetric method was established to determine the lactone and carboxylate molecular states of SN‐38 plasma levels in rats and the cell membrane transfer kinetics in A549 cell lines.